Cyclical dynamics in a Kaleckian model with demand and distribution regimes and endogenous natural output. (26th November 2019) - Nishi, Hiroshi; Stockhammer, Engelbert
Abstract: We analyse the interaction of demand and income distribution in a dynamic Kaleckian model with endogenous natural output. Endogenous changes of the natural output level to changes in the demand‐determined actual output level have featured prominently in discussions of hysteresis after the crisis of 2008. We consider wage‐led and profit‐led demand (PLD) regimes and goods market‐led and labour market‐led income distribution regimes. The stability of the steady state is related to the endogeneity of natural output level in certain regimes. Limit cycles arise when the strong flexibility of prices or wages to the output gap is combined with moderate natural output hysteresis. A Kaleckian model with a wage‐led demand regime and anticyclical profit share is less unstable and pseudo‐Goodwin cycles can arise in the PLD regime with a procyclical profit share.